Pelaksanaan Parate Executie Terhadap Objek Hak Tanggungan Berdasarkan UU No.4 Tahun 1996 Tentang Hak Tanggungan - Syakirah Salsabila; Syaddan Dintara Lubis (Dinasti Review Publisher, 2024)
This article discusses the implementation of parate execution of Mortgage Rights based on Law No. 4 of 1996 in Indonesia. The urgency of this study lies in the importance of providing legal certainty and protection of the rights of creditors and debtors in the auction execution process, which is a primary mechanism in resolving non-performing loans. Issues raised include the potential misuse of rights by creditors, the limited space for debtors to raise objections, and the lack of stringent supervisory mechanisms in the execution auction process. To address these issues, the research method used is a case study on the execution auction of Mortgage Rights at the State Wealth and Auction Service Office (KPKNL) in Medan. This study analyzes the auction implementation procedures, document verification, auction announcements, and the auction execution itself, as well as reviewing related court decisions. The research findings indicate that the execution auction process of Mortgage Rights at KPKNL Medan has been conducted in accordance with the provisions of Law No. 4 of 1996. Open auction announcements through print and electronic media, as well as open bidding, ensure transparency and wide public participation. However, the study also found criticisms regarding the potential misuse of rights by creditors and the lack of protection for debtors. To address these issues, more detailed regulations and stricter supervisory mechanisms are recommended, including the involvement of independent supervisory bodies, to ensure fairness and transparency in the execution auction of Mortgage Rights. These findings underscore the importance of balancing the interests of creditors and debtors in the execution auction process, as well as the need to improve supervisory mechanisms to prevent potential abuse and conflicts.